PENGARUH PARTISIPASI ANGGARAN, KARAKTERISTIK TUJUAN ANGGARAN, DAN GAYA KEPEMIMPINAN TERHADAP KINERJA ANGGARAN PADA PEMERINTAH KABUPATEN ACEH BESAR - Fran Giska Fadhiya Haya; Jhon Andra Asmara; Rulfah M Daud (Jurnal Ilmiah Mahasiswa Ekonomi Akuntansi, 2022)
The purpose of this study is to see how participation in budgets, budgetary target features, and leadership style affect budget performance. The study's population is a Regional Work Unit (SKPD) in Aceh Besar District, which was sampled using the purposive sampling methodology. The Head of Service, Head of the Finance Section, and Technical Implementation Officer of Activities represented by the Head of Planning at 34 SKPD Aceh Besar District were the respondents in this study. They were structural officials involved in the creation and implementation of the budget. Multiple linear regression analysis was used to analyse the data in this study, which was done with the help of the statistical programme SPSS version 25.The results showed that (1) budget participation, budgetary goals characteristics, and leadership style had a simultaneous effect on budget performance, (2) budget participation had no effect on budget performance. budget performance, (3) budgetary goal characteristics affect budget performance, (4) leadership style affects budget performance.